A domain-agnostic ontology for unified metrology data management. (December 2021) - Hippolyte, Jean-Laurent; Chrubasik, Michael; Brochu, Frédéric; Bevilacqua, Maurizio
Abstract: Τhe National Physical Laboratory's (NPL) impact on science, economy and well-being largely relies on proper dissemination and exploitation of scientific evidence from data. Measurement data and software that generates it must therefore implement the Findable, Accessible, Interoperable and Reusable principles (FAIR), whilst enabling data traceability, uncertainty, intellectual property protection and compliance with legislation. Semantic web technologies are ideally suited to support such a unified measurement description through deeply ingrained knowledge sharing and data curation capabilities. This paper presents a semantic-based research approach to data and metadata management which aims to unify the organisation of scientific and engineering digital resources across NPL laboratories and engineering services through the development of a domain-agnostic measurement ontology (DAMO). The ontology development is elucidated using a tailored ontology engineering methodology (OEM) applying an agile and iterative approach based on previously published OEMs. Finally, the use of DAMO is demonstrated through three laboratory-based case studies.